2009
DOI: 10.1016/j.progsolidstchem.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, structure and kinetics in the system Ga–O–N

Abstract: In situ XAS Nucleation Non-stoichiometry Amorphous oxide Insulator-metal transition a b s t r a c t Within the ternary system Ga-O-N we performed experimental and theoretical investigations on the thermodynamics, structure and kinetics of new stable and metastable compounds.We studied the ammonolysis of b-Ga 2 O 3 at elevated temperatures by means of ex situ X-ray diffraction, ex situ neutron diffraction, and in situ X-ray absorption spectroscopy (XAS). From total diffraction pattern refinement with the Rietve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…Since both GaN and Ga 2 O 3 are thermodynamically more stable than the oxynitride phase, the nitridation of Ga 2 O 3 or the oxidation of GaN do not yield to an oxynitride under thermodynamic reaction control [10]. Experimental and theoretical investigations on the ternary system Ga-O-N confirmed that no crystalline or amorphous oxynitride phases appear during these reactions [17]. Synthesis of GaON was successfully obtained by nitridation under NH 3 flow of other gallium precursors such as Ga(OH) 3 [7,12] or NiGa 2 O 4 [5,6].…”
Section: Oxinitreto De Zinco E Gálio Foi Sintetizado Por Meio Da Nitrmentioning
confidence: 99%
“…Since both GaN and Ga 2 O 3 are thermodynamically more stable than the oxynitride phase, the nitridation of Ga 2 O 3 or the oxidation of GaN do not yield to an oxynitride under thermodynamic reaction control [10]. Experimental and theoretical investigations on the ternary system Ga-O-N confirmed that no crystalline or amorphous oxynitride phases appear during these reactions [17]. Synthesis of GaON was successfully obtained by nitridation under NH 3 flow of other gallium precursors such as Ga(OH) 3 [7,12] or NiGa 2 O 4 [5,6].…”
Section: Oxinitreto De Zinco E Gálio Foi Sintetizado Por Meio Da Nitrmentioning
confidence: 99%
“…This article replaces the version published on 10th January 2011, which contained errors in eqn (9).…”
Section: Note Added After First Publicationmentioning
confidence: 99%
“…Recently Nagarajan et al reported that strongly oxygen decient gallium oxide, GaO x , shows a new type of chemically driven insulator-metal transition, once prepared in an amorphous form by pulsed laser deposition. 1,2 In fact, amorphous phases with a composition roughly described by GaO 1.2 and with electrically insulating behavior showed conductivity jumps of several orders of magnitude upon heating. This phenomenon is related to an internal redox disproportionation reaction, leading to the precipitation and growth of transparent and insulating Ga 2 O 3 nuclei in the GaO x matrix, which loses even more oxygen.…”
Section: Introductionmentioning
confidence: 99%